Demonstration reaches: Looking back whilst moving forward with river rehabilitation under the Native Fish Strategy. (March 2014) - Boys, Craig A.; Lyon, Jarod; Zampatti, Brenton; Norris, Andrew; Butcher, Adam; Robinson, Wayne; Jackson, Peter
Summary: 'Demonstration reaches' are sections of river where multiple threats to native fish are addressed through river rehabilitation and strong community participation. They are an important way of promoting the key driving actions of the Murray‐Darling Basin Authority's Native Fish Strategy (NFS) by using on‐ground community‐driven rehabilitation. Measuring rehabilitation success against well‐defined targets and using this information to adaptively mange activities is fundamental to the demonstration reach philosophy. Seven years on from the establishment of the first demonstration reach, there are now seven throughout the Murray‐Darling Basin (MDB), all in differing states of maturation and but all applying a standardised framework for monitoring native fish outcomes. In this study, we reflect on the role that demonstration reaches have played within the NFS, synthesise some key findings from 32 monitoring and evaluation outputs, and highlight some of the successes and barriers to success. We make recommendations as to how to strengthen the demonstration reach model to ensure it remains a relevant approach for fish habitat rehabilitation beyond the NFS and MDB.